THE EFFECTIVENESS OF ELSA SPEAKING APPLICATION IN IMPROVING ENGLISH PRONUNCIATION (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The use of technology has become an important part of the learning language. It helps the teachers to make the effective and attractive teaching language process. Therefore, this paper investigated the effectiveness of Elsa application in improving English pronunciation of students in junior high school level and described how the students’ attitudes toward the use of Elsa application in learning English pronunciation. The data were collected by using tests including pretest and post- test, and then they were analyzed quantitatively. Based on the result of tests, it was found that t-count is higher than t-table (2.92 > 1.6773) in level of sigificant 005. It indicates that Ho was refused and Ha was accepted which means Elsa application is effective in improving students’ pronunciation. Furthermore, the result taken from questionnaire shows that the students shows positive attitude toward the use of Elsa app in learning English pronunciation. Therefore, it can be stated that Elsa app is not only effective to use in teaching pronunciation but also effective in maintaining students’ attitude in learning English pronunciation. Thus, to enrich the literature on teaching English, the writers suggest that the English teacher to use any application to improve students’ English proficiency.